Seismic background noise analysis of BRTR (PS-43) array - Bakır, Mahmure Ezgi. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2012., 2012)
The seismic background noise variation of BRTR array, composed of two sub arrays located in Ankara and in Kırıkkale-Keskin, has been investigated by calculating Power Spectral Density and Probability Density Functions for seasonal and diurnal noise variations between 2005 and 2011. PSDs were computed within the frequency range of 100 s – 10 Hz. The results show us a little change in noise conditions in terms of time and location. Especially, noise level changes were observed at 3-5 Hz in diurnal variations at Keskin array and there is a 5-7 dB difference in day and night time in cultural noise band (1-10 Hz). On the other hand, noise levels of medium period array are high in 1-2 Hz frequency range. High noise levels were observed in daily working times when we compared to night-time in cultural noise band. The seasonal background noise variation at both sites also shows very similar properties to each other. Since both arrays consist of borehole instruments and away from the coasts, we saw a small change in noise levels caused by microseism. Comparison between Keskin short period array and Ankara medium period array show us Keskin array is quiter than Ankara array. Finally, to analyze contribution of BRTR array to IMS network for detection capabilities, six-year long event bulletin data were retrieved between 2005 and 2011 to create annual seismic detection threshold maps for BRTR. The contribution of BRTR array to IMS is related to distance and data availability of array. These results also depend on the changes in IMS network configuration and IMS network stations data availability.
Keywords: Gravitational waves -- Mathematical models.